Influence of Influencers and Capital on Gen Z Stock Decisions via Risk - Sihombing, Rio Danuarta; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study examines the influence of social media influencers and capital availability on stock investment decisions among Generation Z in Jakarta, with risk perception as an intervening variable. Generation Z's growing interest in stock investment is often driven by the persuasive power of social media influencers and accessibility to capital, both of which play crucial roles in shaping investment decisions. Utilizing a quantitative approach, data were collected through questionnaires with Likert-scale responses. The findings suggest that influencers and capital availability positively impact investment decisions, moderated by individuals' risk perceptions. Specifically, risk perception plays a significant role in mediating the relationship, indicating that Generation Z investors weigh potential risks even when guided by influencers or provided with accessible capital. This study offers valuable insights for financial advisors and platforms targeting young investors, underscoring the importance of responsible influencer content and accessible financial resources in promoting informed investment choices.